2013
DOI: 10.5713/ajas.2012.12371
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Slaughter Season on the Fatty Acid Profile in Four Types of Fat Deposits in Crossbred Beef Bulls

Abstract: The objective of this study was to determine the effect of slaughter season on the fatty acid profile in four types of fat deposits in crossbred (Polish Holstein Friesian Black-and-White×Limousine) beef bulls. The percentage share of fatty acids was determined by gas chromatography and were divided into the following categories of fatty acids: saturated (SFAs), unsaturated (UFAs), monounsaturated (MUFAs), polyunsaturated (PUFAs), desirable hypocholesterolemic (DFAs) and undesirable hypercholesterolemic (OFAs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
2
9
1
Order By: Relevance
“…The potential healthfulness of GFB is one of the primary drivers of consumer interest in the product [29]. Research on GFB has mainly focused on its low ratio of n-6 to n-3 FAs [4,7,13,22]. A 2:1 n-6 to n-3 dietary ratio is considered ideal [30], however, typical 'western diets' are estimated to be 20:1 and grain-finished beef have reported ratios up to 13.6:1 [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential healthfulness of GFB is one of the primary drivers of consumer interest in the product [29]. Research on GFB has mainly focused on its low ratio of n-6 to n-3 FAs [4,7,13,22]. A 2:1 n-6 to n-3 dietary ratio is considered ideal [30], however, typical 'western diets' are estimated to be 20:1 and grain-finished beef have reported ratios up to 13.6:1 [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cattle finished in spring rather than fall have higher n-3 FAs [12]. Finishing in spring also increases the saturated FA (SFA) stearic acid, and the monounsaturated FA (MUFA) oleic acid in beef tissue [12,13]. Stearic acid has a net neutral effect on serum cholesterol unlike the SFAs palmitic and myristic acid, which are associated with increases in serum LDL cholesterol [14].…”
Section: Introductionmentioning
confidence: 99%
“…Bilik et al (2009) showed that the fatty acid composition of meat from bulls was more favourable when they were fattened SI with a greater proportion of bulky feeds in the diet, compared with I fattening. Furthermore fat from cattle slaughtered in the summer season has a higher nutritional value and more health-promoting properties (Sobczuk-Szul et al, 2013). De Smet et al (2000), feeding maize silage and concentrate, demonstrated that an increased fat content of bovine meat was paralleled by increased proportions of SFAs and MUFAs and a decreased proportion of PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The consumer market values attributes such as palatability (tenderness, flavor, and juiciness), appearance (color, firmness, and marbling), convenience (cut or sliced product), and health and nutrition (protein, cholesterol, and other benefits) (Sobczuk-Szul et al, 2013). However, the consumption of red meat has been linked to the onset of cardiovascular diseases, hypertension, and obesity (Sobczuk-Szul et al, 2013). As a result, consumer interest in foods with desirable nutritional characteristics and health benefits has been rising.…”
Section: Introductionmentioning
confidence: 99%